Pengaruh Artificial Intelligence (AI) terhadap Efektivitas Proses Pembelajaran di Era Digital - Pendiasari, Ni Luh Candy (Cognoscere: Jurnal Komunikasi dan Media Pendidikan, 2026)
This systematic literature review (SLR) analyzes the influence of Artificial Intelligence (AI) on learning effectiveness in the digital era by reviewing 33 key academic references. Utilizing the PRISMA protocol, this study synthesizes findings regarding cognitive impacts, student engagement, and the ethical challenges of AI integration in education. Meta-analysis results indicate an overall effect size of , with Generative AI and chatbot technologies achieving the highest performance at . In Indonesia, AI implementation has significantly improved students' critical thinking skills, raising average scores from 47.13 to 75.96. However, the study reveals a "Crutch Effect" paradox, where over-reliance leads to a 17% performance drop in unassisted exams. Other systemic challenges include the risk of "Cognitive Surrender" and the digital divide in 3T (underdeveloped, outermost, and frontier) regions. In conclusion, AI serves as a catalyst for learning effectiveness, the success of which is mediated by pedagogical design and human-AI synergy. The adoption of Socratic AI models is recommended to preserve learners' cognitive agency. Abstrak Tinjauan literatur sistematis (SLR) ini menganalisis pengaruh Kecerdasan Buatan (AI) terhadap efektivitas pembelajaran di era digital dengan meninjau 33 referensi akademik utama. Menggunakan protokol PRISMA, penelitian ini mensintesis dampak kognitif, keterlibatan siswa, serta tantangan etis integrasi AI dalam pendidikan. Hasil meta-analisis menunjukkan ukuran efek keseluruhan sebesar , dengan teknologi AI Generatif dan chatbot mencatat performa tertinggi sebesar . Di Indonesia, implementasi AI terbukti meningkatkan kemampuan berpikir kritis siswa secara signifikan dari skor rata-rata 47,13 menjadi 75,96. Namun, studi ini mengungkap paradoks "Crutch Effect" di mana ketergantungan berlebihan memicu penurunan performa sebesar 17% pada ujian tanpa bantuan AI. Tantangan sistemik lainnya mencakup risiko "Cognitive Surrender" dan kesenjangan digital di wilayah 3T. Kesimpulannya, AI berperan sebagai katalisator efektivitas pembelajaran yang keberhasilannya dimediasi oleh desain pedagogis dan sinergi manusia-AI. Disarankan pengadopsian model Socratic AI untuk menjaga agensi kognitif peserta didik. Kata Kunci: Kecerdasan Buatan, Efektivitas Pembelajaran, Systematic Literature Review, Berpikir Kritis, Era Digital.